Maturity Level Analysis of the BAZNAS Sukabumi Regency Website using the COBIT 2019 Framework in the BAI02 Domain - yuniar, siti rahma; saepudin, sudin; satria, hendri eka (Sistemasi: Jurnal Sistem Informasi, 2025)
The BAZNAS Sukabumi Regency website plays a vital role in supporting transparent and efficient digital zakat services. However, challenges remain in updating features and optimizing the management of information system requirements, which hinder full digital transformation. These issues highlight the need for an evaluation of the maturity level of the information systems in use. This study aims to assess the maturity level of information system requirements management on the BAZNAS Sukabumi Regency website using the COBIT 2019 framework, specifically within the BAI02 domain (Managed Requirements Definition). The research methodology includes observation, interviews, and literature review, analyzed based on the capability level model in COBIT 2019. The findings indicate that the maturity level is at Level 3 (Established Process), which means the processes are standardized, documented, and consistently implemented. However, there is a gap compared to the desired (TO-BE) state of Level 4 (Predictable), particularly in areas such as monitoring, performance measurement, and quantitative and systematic risk management. The study concludes that while the BAZNAS Sukabumi Regency website demonstrates good information system management practices, improvements are still needed in control mechanisms, continuous performance measurement, and periodic evaluations. Recommendations focus on enhancing governance practices, strengthening performance metric documentation, and developing strategies to sustainably improve information system capabilities.